ABSTRACT - Jeklien Koraag; Dwi Setiawan (Kata Kita: Journal of Language, Literature, and Teaching, 2014)
In this project, I would like to expose the reality happening in the Indonesian society through Science fiction graphic novel script and samples. This project focuses on how the live of my main character that represent particular condition of an individual in the society. It also focuses on the surival of the character as the individual in changing her future. The theme that is used in this project is the survival of the individual. I would also explore how fear distorted human in making a crucial decision in order to survive the adverse and unusual circumstance. To depict this reality through fiction, I am using the Timepunk, a sub-genre of science fiction as the genre of my work and bringing out the issue of the cure of leukemia as the main concern of my main character.